Teknik Tatap – Landas di Sentang, Tanjung Tiram, Batubara, Sumatera Utara (Teknik Pembuatan Tembikar Tradisi Neolitik) - Eny Christyawaty (Balai Arkeologi Sumatera Utara, 2010)
AbstractPottery is one of the old cultural product when people lived in prehistoric times. Humans have known and to make pottery from clay material since humans feel the need for containers for storing and cooking food. Pottery has a very important role in society life. Making pottery with a paddle anvile technique is a technique known in neolithic culture. Until now, these techniques are still used in several places in Indonesia, such as in Sentang, Tanjung Tiram, North Sumatera